since this is a section where a lot of people seems to be interested in, I came across a problem on my adv. algebra 2 test today that I couldn't solve!!! And it bugs me that I couldn't solve it!!! :evil: Can anyone help me???

here it is:

Solve for "x"

a(x-3)+8 = b(x-1)

The answer is there if you google search.

oh :oops: haha well I thought you guys would have more fun trying to figure it out! lol but it seems like it's a pretty easy thing now that I saw it!

a(x - 3) + 8 = b(x - 1)

ax - 3a + 8 = bx - b

ax - bx = 3a - b - 8

x(a - b) = 3a - b - 8

x = (3a - b - 8 ) / (a - b)